Girls' attentive traits associate with cerebellar to dorsal attention and default mode network connectivity. (April 2019) - Rohr, Christiane S.; Dimond, Dennis; Schuetze, Manuela; Cho, Ivy Y.K.; Lichtenstein-Vidne, Limor; Okon-Singer, Hadas; Dewey, Deborah; Bray, Signe
Abstract: Attention traits are a cornerstone to the healthy development of children's performance in the classroom, their interactions with peers, and in predicting future success and problems. The cerebellum is increasingly appreciated as a region involved in complex cognition and behavior, and moreover makes important connections to key brain networks known to support attention: the dorsal attention and default mode networks (DAN; DMN). The cerebellum has also been implicated in childhood disorders affecting attention, namely autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD), suggesting that attention networks extending to the cerebellum may be important to consider in relation to attentive traits. Yet, direct investigations into the association between cerebellar FC and attentive traits are lacking. Therefore, in this study we examined attentive traits, assessed using parent reports of ADHD and ASD symptoms, in a community sample of 52 girls aged 4–7 years, i.e. around the time of school entry, and their association with cerebellar connections with the DAN and DMN. We found that cortico-cerebellar functional connectivity (FC) jointly and differentially correlated with attentive traits, through a combination of weaker and stronger FC across anterior and posterior DAN and DMN nodes. These findings suggest that cortico-cerebellar integration may play an important role in the manifestation of attentive traits. Highlights: We explored young children's cerebellar-cortical FC in relation to attentive traits. Attentive traits were assessed in 4–7 year old girls via validated parent reports. The analysis focused on the dorsal attention (DAN) and default mode network (DMN). Inattention/attention switching positively related to Crus I-prefrontal DAN/DMN FC. Attention switching negatively related to Crus I-parietal DAN/DMN FC.